2008
DOI: 10.1148/radiol.2482071496
|View full text |Cite
|
Sign up to set email alerts
|

Human Breast Cancer Tumor Models: Molecular Imaging of Drug Susceptibility and Dosing during HER2/neu-targeted Therapy

Abstract: Purpose:To use near-infrared (NIR) optical imaging to assess the therapeutic susceptibility and drug dosing of orthotopic human breast cancers implanted in mice treated with molecularly targeted therapy. Materials and Methods:This study was approved by the institutional animal care and use committee. Imaging probes were synthesized by conjugating the human epidermal growth factor receptor type 2 (HER2)-specific antibody trastuzumab with fluorescent dyes. In vitro probe binding was assessed with flow cytometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 29 publications
0
50
0
1
Order By: Relevance
“…Orthotopic models have previously been successfully used for evaluation of trastuzumab therapy for other tumor types (40)(41)(42). The efficacy of trastuzumab on HER-2-positive breast cancer has been shown in vitro and in orthotopic models as well as clinically in breast cancer patients (6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Orthotopic models have previously been successfully used for evaluation of trastuzumab therapy for other tumor types (40)(41)(42). The efficacy of trastuzumab on HER-2-positive breast cancer has been shown in vitro and in orthotopic models as well as clinically in breast cancer patients (6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Research has also demonstrated that fluorescent dye-labeled trastuzumab enabled differentiation between breast cancer cells expressing high and low levels of HER2. Serial imaging before and during trastuzumab therapy revealed a significant reduction in probe uptake with treatment (Gee et al, 2008). Trastuzumab was also used to mediate the cellular internalization of pH-activatable fluorephores.…”
Section: Wwwintechopencom Targeting Egfr and Her2 For Molecular Imamentioning
confidence: 99%
“…Fluorescent detection techniques using fluorescencelabelled trastuzumab [39] and HER-2 Affibody [40] have also been applied to the detection of tumour response to trastuzumab therapy. Gee et al [39] administered trastuzumab conjugated to the NIR (near infrared) dye CY5.5 to nude mice bearing xenografts derived from breast tumour cell lines expressing high and normal levels of HER-2.…”
Section: Optical Probesmentioning
confidence: 99%
“…Gee et al [39] administered trastuzumab conjugated to the NIR (near infrared) dye CY5.5 to nude mice bearing xenografts derived from breast tumour cell lines expressing high and normal levels of HER-2. They showed that fluorescence detected by a whole-body multichannel imaging system on the surface of mice above the tumours corresponded with HER-2 expression.…”
Section: Optical Probesmentioning
confidence: 99%
See 1 more Smart Citation